1994
DOI: 10.1161/01.res.74.6.1114
|View full text |Cite
|
Sign up to set email alerts
|

Triamterene inhibits the delayed rectifier potassium current (IK) in guinea pig ventricular myocytes.

Abstract: In humans, proarrhythmia during therapy with action potential-prolonging drugs can be associated with hypokalemia often provoked by concomitant administration of diuretic agents. Consequently, therapy with class III antiarrhythmics and K'-sparing diuretics, such as triamterene, may be indicated. Triamterene, along with its K'-sparing properties, exhibits other pharmacological effects. In the heart, it can increase action potential duration (guinea pig atria and papillary muscles), protect against reperfusion-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 27 publications
4
16
0
Order By: Relevance
“…Nifedipine and nisoldipine were applied at concentrations of 5 and 0.2 mol/L, respectively, both sufficient to achieve almost complete blockade of I CaL , 17 as also verified in the setting of the present study (data not shown). The effect of inhibiting Ca 2ϩ influx was also tested by lowering extracellular Ca 2ϩ concentration from 2 to 0.5 mmol/L (low Ca 2ϩ solution) and replacing it with Mg 2ϩ (see "Materials and Methods").…”
Section: Effect Of I Ca Inhibition On I Ba and I 0k During The Ventrisupporting
confidence: 85%
“…Nifedipine and nisoldipine were applied at concentrations of 5 and 0.2 mol/L, respectively, both sufficient to achieve almost complete blockade of I CaL , 17 as also verified in the setting of the present study (data not shown). The effect of inhibiting Ca 2ϩ influx was also tested by lowering extracellular Ca 2ϩ concentration from 2 to 0.5 mmol/L (low Ca 2ϩ solution) and replacing it with Mg 2ϩ (see "Materials and Methods").…”
Section: Effect Of I Ca Inhibition On I Ba and I 0k During The Ventrisupporting
confidence: 85%
“…Our data both confirm the original observations and, more importantly, expand on them with respect to the addition of the QT interval analysis. The fact that propofol at concentrations less than 10 M had no significant effect on the QT C indicates that the observed slowing was not due to propofol-mediated inhibition of the cardiac I Ks current, which would prolong QT C because of delayed repolarization (Daleau and Turgeon, 1994), consistent with previous reports of a much lower sensitivity of I Ks channels to propofol (IC 50 of 250 M) (Heath and Terrar, 1997). Thus, the slowing of sinus rate observed both by us and others with low micromolar concentrations of propofol is probably due to propofol impairment of HCN channel function.…”
Section: Discussionmentioning
confidence: 93%
“…), 8,9,[15][16][17][18][19][20] prolong action potential duration by selectively blocking I Kr , whereas other drugs, such as indapamide or triamterene, block preferentially I Ks . 21,22 Drug-induced LQTS is often observed under conditions of impaired drug elimination as it was first described for the drug-drug interaction between the histamine H1-antagonist terfenadine and the macrolide antibiotic erythromycin. 23 Indeed, these events were explained mostly through an inhibition of terfenadine CYP3A-mediated metabolism by erythromycin (CYP3A inhibitor).…”
Section: Introductionmentioning
confidence: 99%